(untitled) (Journal of Social Economics Research, 2019)
In Ethiopia, MSEs have become the favorite of policy makers as they are believed to play a critical role in addressing both poverty reduction and economic growth goals. Over the years, while some MSEs have grown extremely large and profitable, many others have failed or have not been as successful as they might have been. This study seeks to identify the factors that hamper the success of Micro and Small Enterprises in Amhara region of Ethiopia since studies aimed at assessing the same are virtually missing. This study employed a quantitative research approach using a descriptive survey design. The data was drawn from a survey of 316 MSEs in Amhara region, Ethiopia. Statistical models including One Way Analysis of Variance (ANOVA) and T-test are used to analyze the data apart from other descriptive statistics such as percentages and mean. The study has revealed that working premises, marketing and financial factors are the three most serious factors that hamper the success of MSEs. We suggest that since the real challenges of MSEs change over time, the challenges of MSEs must be studied at some periodic interval to identify the real challenges of MSEs of the time and take appropriate action timely.